Solar energy utilization techniques, policies, potentials, progresses, challenges and recommendations in asean countries - Pandey, Ashutosh K.; Kalidasan, B.; Reji Kumar, Rajamony; Rahman, Saidur; Tyagi, Vineet Veer; Krismadinata, Krismadinata; Said, Zafar; Salam, P. Abdul; Juanico, Dranreb Earl; Ahamed, Jamal Uddin; Sharma, Kamal; Samykano, Mahendran; et al. (MDPI, 2022)
Sustainable development goals not only contributes towards a clean environment but also towards better climatic conditions. Within Asia next to China and India, the Association of Southeast Asian Nations (ASEAN) are the actively developing countries in terms of economy and technologies. On the verge of achieving development, the ASEAN countries highly depend on fossil fuels for their energy needs. The ASEAN countries have taken visionary steps towards increasing the renewable energy mix with the conventional grid without hampering the ongoing development; this study presents the solar energy utilization policies, potential, progresses, and challenges adopted in ASEAN countries; furthermore, in these nations there is a huge potential of solar energy being located near the equator, therefore, they should focus on both solar to electrical and solar to thermal energy applications; however, in order to meet the peak demand and ensure the reliability of renewable energy like solar power, the development of advanced energy storage systems could be the key areas, and concrete efforts are required. Therefore, this article is a spotlight on government policies and goals focusing on energy potential, major progress in terms of energy storage and challenges in implementation of renewable energy systems in ASEAN countries; furthermore the recommended highlights on policies to accelerate the exploitation of renewable energy usage among the people are also discussed in detail, besides, the insights on reduction of carbon footprints over the next decade through incorporation of advanced energy storage systems. The issues discussed in this article will be helpful for exploring the desired energy storage systems and energy policies to be followed, which will eventually attract the stakeholders for small and medium-scale entrepreneurs for the development of renewable energy business in the region, if implemented on the ground.